UJI COBA PEDOMAN APLIKASI PERUMUSAN PESAN UMUM GIZI SEIMBANG (PUGS) SESUAI KONDISI DAERAH - Tjetjep Syarif Hidayat; Abas Basuni Jahari (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2009)
Test The Guidance For The Impelentation of "Dietary Guidelines" For Different Area Conditions.Background: Dietary guidelines for nutrition education tool developed by the health department until now still difficult in the field. Dietary guidelines should be arranged by local officials. Guidelines that needs to be made how to craft a balanced nutrition messages in accordance with local conditions.Objectives: To develop a guidance on how to implement the PUGS which is suitable for the local conditions.Methods: Exploratory research methods as applied research for local officials. Implematation manual has been composed PUGS who first disseminated to local officials at the district level. And than local officials to practice through the following stages; how do identify nutritional problems and then how to make balanced nutrition messages in accordance with local conditions. This guidance was tested in the district of Tasikmalaya, West Java and Magelang of Central Java.Results: Showed that there was a significant difference after and before test the guidance for the implementation of dietary guidelines in local officers were able to identify nutrition problems and to develop messages on PUGS.Keywords: PUGS, implementation of dietary guidelines and local condition.